Preferences of patients for patient centred approach to consultation in primary care: observational study - Little, Paul (BMJ, 2001)
OBJECTIVE: To identify patient's preferences for patient centred consultation in general practice. DESIGN: Questionnaire study. SETTING: Consecutive patients in the waiting room of three doctors' surgeries. MAIN OUTCOME MEASURES: Key domains of patient centredness from the patient perspective. Predictors of preferences for patient centredness, a prescription, and examination. RESULTS: 865 patients participated: 824 (95%) returned the pre-consultation questionnaire and were similar in demographic characteristic to national samples. Factor analysis identified three domains of patient preferences: communication (agreed with by 88-99%), partnership (77-87%), and health promotion (85-89%). Fewer wanted an examination (63%), and only a quarter wanted a prescription. As desire for a prescription was modestly associated with desire for good communication (odds ratio 1.20; 95% confidence interval 0.85 to 1.69), partnership (1.46; 1.01 to 2.09), and health promotion (1.61; 1.12 to 2.31) this study may have underestimated preferences for patient centredness compared with populations with stronger preferences for a prescription. Patients who strongly wanted good communication were more likely to feel unwell (very, moderately, and slightly unwell; odds ratios 1, 0.56, 0.39 respectively, z trend P<0.001), be high attenders (1.70; 1.18 to 2.44), and have no paid work (1.84; 1.21 to 2.79). Strongly wanting partnership was also related to feeling unwell, worrying about the problem, high attendance, and no paid work; and health promotion to high attendance and worry. CONCLUSION: Patients in primary care strongly want a patient centred approach, with communication, partnership, and health promotion. Doctors should be sensitive to patients who have a strong preference for patient centredness—those vulnerable either psychosocially or because they are feeling unwell.